Association Between CD24-P226-C/T Polymorphism and Multiple Sclerosis: A Meta-Analysis. (May 2015) - Jiang, Longyang; Bai, Xuefeng; Wang, Yan; Wei, Minjie
Abstract : Background : Multiple sclerosis (MS) is a progressive inflammatory and neurodegenerative disease of the central nervous system (CNS), the etiology of which is still uncertain. Several case-control studies investigated the association between CD24-P226-C/T polymorphism and MS risk, and these studies have shown inconsistent results. Objective : To address the association of CD24-P226-C/T polymorphism with MS risk by meta-analysis. Methods : A comprehensive search was conducted to identify all eligible studies of CD24-P226-C/T polymorphism and MS risk up to July 2013. The odds ratios (ORs) of CD24 allele distributions in MS were analyzed against controls. Results : In total, seven case-control studies with 949 cases of MS and 1177 controls were included in this meta-analysis. The overall results showed a significant association between CD24-P226-C/T polymorphism and MS susceptibility under homozygote comparison model (OR = 2.496, 95% CI = 1.813–3.435, p < 0.0005), dominant model (OR = 1.367, 95% CI = 1.147–1.629, p < 0.0005), recessive model (OR = 2.305, 95% CI = 1.700–3.126, p < 0.0005) and allelic model (OR = 1.422, 95% CI = 1.244–1.625, p < 0.0005). However, no significant association was observed under heterozygous comparison model (OR = 1.182, 95% CI = 0.982–1.423, p = 0.078). Conclusions : This meta-analysis indicates that CD24 P266-C/T polymorphism is more associated with the risk of MS than healthy controls. However, due to the small sample size in most of the included studies, additional large-scale and well-designed case-control studies were required for the validation of this association.